Halo phenomenon with regression of acquired melanocytic nevi : a case report - Radoš, Jaka; Paštar, Zrinjka; Lipozenčić, Jasna; Ilić, Ivana, patologinja; Štulhofer-Buzina, Daška (2009)
Summary
Bibliografija: 16 jed
Keywords: Halo nevus -- Melanocitna lezija